MANFAAT SOSIAL DAN NILAI-NILAI TRADISI SEDEKAH BUMI PERSPEKTIF TEORI FUNGSIONALISME - Rubai, Ahmad; Mohammad Rofiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to analyze the benefits of the values embedded in the implementation of the sedekah bumi tradition through the perspective of functionalism theory. The sedekah bumi tradition, as part of Indonesia’s cultural heritage, plays an important role in strengthening social relationships and creating balance within community life. Through a functionalist approach, this tradition is understood as a social system that functions to maintain social order and stability. Sedekah bumi is not merely interpreted as a customary ritual, but also as a social mechanism that fosters solidarity among community members, strengthens togetherness, and builds social integration within a diverse society. The functionalist perspective is used to examine how this tradition contributes to maintaining social stability, reducing potential conflicts, and regulating the relationship between humans and nature. It also serves as a collective expression of gratitude for agricultural yields while reinforcing awareness of the importance of environmental balance. The data collection process in this article was conducted through a literature study by reviewing and exploring various books, journals, and documents, both printed and electronic, that are relevant to the topic. The findings indicate that the values contained in sedekah bumi—such as faith (aqidah), worship (ibadah), social, cultural, and philosophical values—make a significant contribution to maintaining social harmony and strengthening the relationship between humans, fellow community members, and the natural environment in a sustainable manner. Keywords: Earth almsgiving tradition, Functionalism theory